The comparative method reviewed : regularity and irregularity in language change - Durie, Mark, 1958-; Ross, Malcolm (Oxford University Press, 1996)
Historical reconstruction of languages relies on the comparative method, which itself depends on the notion of the regularity of change. The regularity of sound change is the famous Neogrammarian Hypothesis: "sound change takes place according to laws that admit no exception." The comparative method, however, is not restricted to the consideration of sound change, and neither is the assumption of regularity. Syntactic, morphological, and semantic change are all amenable in varying degrees, to comparative reconstruction, and each type of change is constrained in ways that enable the r.